Chemical composition of total deposition samples collected in the metropolitan area of ​​Costa Rica in 2012 - Herrera, Jorge (2014)
Inorganic ions concentrations were measured on bulk precipitation samples in seven sites in San José, Heredia and Belen cities during the rainy season 2012. SO4-2, NO3-, Cl-, F-, PO4-3, NH4+, K+, Na+, Ca+2, Mg+2 were analyzed by ion chromatography. The results indicated that Na+ and SO42− were the most abundant ions. Pearson's correlation, applied to all data, showed a high correlation between SO42- with NO3-, Ca2+ and NH4+, indicating an anthropogenic and neutralization origin respectively. The contribution of NO3- to neutralization was relatively small in comparison with SO42−. PCA analysis was used in order to indentify the mainly sources (crustal, neutralization and marine aerosol) and that contribute to the chemical composition of the bulk precipitation samples.